The preliminary report about the modified supramalleolar tibial osteotomy for asymmetric ankle osteoarthritis. (19th February 2019) - Koo, Ja Wook; Park, Sang Hoon; Kim, Ki Chun; Sung, Il-Hoon
Objective: Supramalleolar tibial osteotomy (SMO) for asymmetric ankle osteoarthritis (OA) is known to lead to satisfactory. Here, authors present a preliminary report on SMO surgical treatment in patients with asymmetric ankle arthritis. Materials and Methods: We reviewed cases of asymmetric ankle OA treated by modified SMO between January 2011 and October 2015. Clinical assessment was performed with the use of the ankle and hindfoot score of the American Orthopedic Foot and Ankle Society (AOFAS), foot function index, and visual analogue scale (VAS). Patient satisfaction with surgery and postoperative subjective symptoms were examined. Radiographic evaluation included preoperative and postoperative tibial anterior surface angle (TAS angle), talar tilt angle (TT angle), and tibial lateral surface angle (TLS angle). Takakura stage was measured. Results: The average follow-up period was 46.3 months. The AOFAS score was 55.7 ± 6.03 preoperatively and 76.0 ± 4.73 postoperatively. Foot function index was 60.7 ± 8.78 preoperatively and 30.8 ± 7.59 postoperatively. VAS was 7.2 ± 0.53 before surgery and 1.9 ± 0.85 after surgery. Clinical evaluations showed statistically significant improvement. The majority of patients reported satisfactory results in the subjective satisfaction evaluation. TAS angle was 84.6 ± 1.82 preoperatively and 94.0 ± 2.79 postoperatively. TLS angle was 78.8 ± 2.11 preoperatively and 81.8 ± 1.80 postoperatively. TT angle was 3.6 ± 1.26 before surgery and 2.1 ± 0.79 after surgery. Thirteen cases showed radiographic improvement of Takakura stage. Complications were not observed. Conclusion: Modified SMO is a useful procedure that provides for the union and stability of osteotomy with the advantages of the existing SMO and can be performed without bone graft.